The historical significance of the Mediterranean in shaping international norms and legal frameworks - BRAHIMI , Smail (La Revue d’Histoire Méditerranéenne, 2025)
This article offers a detailed examination of how the Mediterranean region has significantly influenced the development of worldwide legal norms and systems throughout history. It follows the evolution of basic legal principles from ancient times to the present, by emphasizing the region’s important role in shaping international law. The study starts with the old maritime laws of the Phoenicians, advances through the complex legal systems of ancient Greece and Rome, and expands to the medieval and Ottoman legal customs that continued to influence local and worldwide standards. The research also examines critical modern aspects, such as the Treaty of Tordesillas determining zones of control among European countries, and the involvement of Mediterranean countries in important global organizations and agreements. The article highlights how the Mediterranean has had a lasting impact on international legal practices by studying various historical and modern impacts, making it clear that this influence is still evident in contemporary international law.